Mora creditoris e imposibilidad sobrevenida de la prestación - Cuena Boy, Francisco (Revista de Derecho, 2019)
One of the effects of the mora creditoris or mora accipiendi is the restriction to dolus of the debtor’s liability for the loss of the thing due, i. e., for the non-fulfilment of his debt derived from the subsequent impossibility of performance. Based on this assumption and considering a set of significant texts, our paper deals with the consequences for the debtor of such impossibility when it takes place during the creditor’s delay and provided there is no fraud or deceit on the debtor’s side. Although the consequences are essentially similar in all sources and all cases which have been analysed, from a technical point of view they follow different processes, depending on the nature of the thing due; that is, depending on whether it is